Pemberdayaan “Remaja Anti Anemia” dalam Pencegahan Anemia Berbasis Pemanfaatan Pangan Lokal di SMAS Adhyaksa 1 - Nurita, Suci Rahmani; Julaecha, Julaecha; Nurfitriani, Nurfitriani; Perwitasari, Tuhu; Nurbaiti, Nurbaiti (Universitas Baiturrahim, 2025)
The prevalence of anemia in adolescent girls is increasing, so other efforts are needed for prevention. One of the factors that influence the occurrence of anemia is iron deficiency. Handling anemia with food ingredients is still rarely done even though it has great potential to prevent anemia, especially in adolescent girls. Based on field observations, there are still adolescents who have signs and symptoms of anemia, education has been carried out regarding anemia but the role of adolescents in preventing anemia has not been active. The community service activity in the form of